The mutual agreement procedure and arbitration of double taxation disputes (2021)
It is in the interest of most states to eliminate double taxation (i.e. the payment of the same tax in two jurisdictions) of transnational commercial enterprises. Because such disputes involve, on the one hand, the state imposition of taxes, a right universally asserted by all states, and private entities on the other, taxation disputes between such parties are not, on their face, easily susceptible to arbitration. This article analyzes two dispute settlement procedures-the OECD First Model Tax Convention and a similar EU Convention-with the exclusive focus on disputes relating to the imposition of double taxation. It will look at the ways in which state roles may vary under these procedures from assisting in the negotiation process to taking a part similar to, but with important differences from, diplomatic protection on behalf of an affected enterprise. The article will examine the situations under which the settlement procedure is required and/or available, how the procedures are triggered, the obligations and parts played by the parties, the means by which the disputes are resolved (from negotiations to tribunals) and the limitations of the procedures. Are they “taxpayer friendly”? As a result the reader may draw comparisons between the two procedures. Finally, the article will look at the proposed OECD Arbitration Clause which is intended to be incorporated into Article 25 of the OECD Model Tax Convention as well as how these mechanisms relate and/or conflict with bilateral tax treaties and the GATS.